Synthesis of Mn2V2O7 nanopebbles via hydrothermal method and its high-efficiency energy storage for supercapacitors. (15th November 2022) - Sethuraman, V.; Kumar, R. Dhilip; Prabhakaran, A.; Rajkumar, P.; Diwakar, K.; Senthilkumaran, M.; Saravanan, M.; Sasikumar, R.; Aravinth, K.; Ramasamy, P.; Manigandan, R.
Abstract: For its improved electrochemical features, such as a longer life cycle, higher specific capacitance, and higher specific power, the supercapacitor has acquired increased attention. Between the battery and the conventional capacitor, the supercapacitor fills the energy and power gaps. The supercapacitor has been suggested as an energy storage device for higher-power uses in the future. MnOOH nanorods and Mn2 V2 O7 nanopebbles were synthesised through a hydrothermal method, and those materials were studied by X-ray diffraction (XRD), thermal graviometric analysis (TGA), Fourier transformed infrared (FT-IR), Raman spectra, X-ray photoelectron spectroscopy (XPS), scanning electron microscope (SEM), and transmission electron microscope (TEM). The XRD results revealed the creation of a monoclinic phase of synthesised MnOOH nanorods and Mn2 V2 O7 nanopebbles. The supercapacitance behaviour of crystalline MnOOH nanorods and Mn2 V2 O7 nanopebbles was examined using electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV), and galvanostatic charge-discharge (GCD) techniques. The Mn2 V2 O7 nanopebbles achieved a high specific capacitance value of 1310 F/g at 0.25 A/g. The assembled asymmetric supercapacitor of Mn2 V2 O7 @NF//AC@NF has a good capacitance retention value of 98 % and matches a coulombic efficiency of 95.5 % over 5000 cycles. In an alkaline medium, the energy density and power density of Mn2 V2 O7 @NF//AC@NF are 53.9 Wh k/g and 1564 W k/g, respectively. Highlights: Mn2 V2 O7 nanopebbles were developed by a hydrothermal method. Physical-chemical and electrochemical properties were studied. High specific capacitance, power density, and energy density values of 1310 F/g, 2948 W k/g, and 36.8 Wh K/g, respectively, were achieved. Mn2 V2 O7 nanopebbles have been found to remain stable until 5000 cycles.